أساسيات كفاءة العمل الإداري: دراسة وصفية تحليلية في تصنيف كفاءات العمل ومقاييسه - Abubaker Ahmed; Mohammad Nashief S. Pisomi (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.